2021
DOI: 10.3390/coatings11070840
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Autologous Bone Marrow Mesenchymal Stem Cells and Platelet-Rich Plasma on Bone Regeneration and Osseointegration of a Hydroxyapatite-Coated Titanium Implant

Abstract: Bone regeneration remains one of the major clinical needs in orthopedics, and advanced and alternative strategies involving bone substitutes, cells, and growth factors (GFs) are mandatory. The purpose of this study was to evaluate whether the association of autologous bone marrow mesenchymal stem cells (BMSC), isolated by ‘one-step surgical procedure’, and activated platelet rich plasma (PRP) improves osseointegration and bone formation of a hydroxyapatite-coated titanium (Ti-HA) implant, already in clinical u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…There are several different types of stem cells involved into the regeneration processes of dental pulp cells, including stem cells of the apical papilla (SCAPs), periodontal ligament stem cells (PDLSCs) and human dental pulp cells (hDPCs) [119,120]. It has already been proven that autologous platelet concentrate may be a carrier for bone marrow mesenchymal stem cells (BMSCs) [121] and may stimulate the processes of proliferation and differentiation of BMSCs [122]. Sequeira et al [123] used PRP as a scaffold for SCAPs and found that SCAPs induced formation of dentin-like and pulp-like tissues.…”
Section: Mesenchymal Stem Cells and Platelet Concentratesmentioning
confidence: 99%
“…There are several different types of stem cells involved into the regeneration processes of dental pulp cells, including stem cells of the apical papilla (SCAPs), periodontal ligament stem cells (PDLSCs) and human dental pulp cells (hDPCs) [119,120]. It has already been proven that autologous platelet concentrate may be a carrier for bone marrow mesenchymal stem cells (BMSCs) [121] and may stimulate the processes of proliferation and differentiation of BMSCs [122]. Sequeira et al [123] used PRP as a scaffold for SCAPs and found that SCAPs induced formation of dentin-like and pulp-like tissues.…”
Section: Mesenchymal Stem Cells and Platelet Concentratesmentioning
confidence: 99%